Ibrah Kisah Penolakan Nabi Yusuf Terhadap Ajakan Imra’at al-Aziz Perspektif Tafsir Maqashidi - Moh. Mauluddin; Khusnul Muttaqin; Ahmad Syafi’i (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2022)
The story of the Prophet Yusuf has always been studied in several aspects, namely aspects of linguistics, educational education, modern literature, and literary psychology. The focus of this research is on the climax of the story contained in verse 23, which tells the story of Prophet Yusuf's rejection of imra'at al-Aziz. This study uses a maqasi>di interpretation approach, an interpretive method that focuses or emphasizes the maqasi>d aspects of the Qur'an. Tafsir maqa>sidi in the verses of the story can be done by doing tadabbur (reflection) and analyzing badi' tauriyyah. The result of this study is the discovery of aspects of maqasid hifd al-di>n, hifd al-nafs, as well as human values ​​and responsibility.